Initial performance of maize in response to humic acids and plant growth-promoting bacteria - BALDOTTO, LILIAN ESTRELA BORGES (Revista Ceres, 2018)
Seed treatment with inoculants based on plant growth-promoting bacteria (PGPB) or the application of humic acids (HA) may increase the productivity of plants of agricultural interest. The hypothesis of this work is that it is possible to combine the effect of plant growth promoting characteristic of HA with the inoculation of PGPB selected strains in the treatment of maize seeds. Thus, providing superior responses than in single applications of both in the initial maize development. To meet this purpose, we conducted isolated application of HA or PGPB inoculation of Burkholderia gladioli and Rhizobium cellulosilyticum, and the combined application of PGPB and HA for treatment of maize seeds. At the end of the experiment (45 days after germination), the plants were evaluated biometrically, nutritionally and a bacteria count was performed in plants using the Most Probable Number technique. The results showed that it is possible to combine the effects of HA with the inoculation of selected strains of PGPB, obtaining superior responses to the isolated application of both. Thus, the use of HA-based bio-stimulants in combination with PGPB is positive and complementary compared to inputs generally used in the treatment of maize seeds.